Is It safe? Nonoperative management of blunt splenic injuries in geriatric trauma patients. Issue 1 (January 2018) - Trust, Marc D.; Teixeira, Pedro G.; Brown, Lawrence H.; Ali, Sadia; Coopwood, Ben; Aydelotte, Jayson D.; Brown, Carlos V.R.
Abstract : BACKGROUND: Because of increased failure rates of nonoperative management (NOM) of blunt splenic injuries (BSI) in the geriatric population, dogma dictated that this management was unacceptable. Recently, there has been an increased use of this treatment strategy in the geriatric population. However, published data assessing the safety of NOM of BSI in this population is conflicting, and well-powered multicenter data are lacking. METHODS: We performed a retrospective analysis of data from the National Trauma Data Bank (NTDB) from 2014 and identified young (age < 65) and geriatric (age ≥ 65) patients with a BSI. Patients who underwent splenectomy within 6 hours of admission were excluded from the analysis. Outcomes were failure of NOM and mortality. RESULTS: We identified 18, 917 total patients with a BSI, 2, 240 (12%) geriatric patients and 16, 677 (88%) young patients. Geriatric patients failed NOM more often than younger patients (6% vs. 4%, p < 0.0001). On logistic regression analysis, Injury Severity Score of 16 or higher was the only independent risk factor associated with failure of NOM in geriatric patients (odds ratio, 2.778; confidence interval, 1.769–4.363; p < 0.0001). There was no difference in mortality in geriatric patients who had successful vs. failed NOM (11% vs. 15%; p = 0.22). Independent risk factors for mortality in geriatric patients included admission hypotension, Injury Severity Score of 16 or higher, Glasgow Coma Scale score of 8 or less, and cardiac disease. However, failure of NOM was not independently associated with mortality (odds ratio, 1.429; confidence interval, 0.776–2.625; p = 0.25). CONCLUSION: Compared with younger patients, geriatric patients had a higher but comparable rate of failed NOM of BSI, and failure rates are lower than previously reported. Failure of NOM in geriatric patients is not an independent risk factor for mortality. Based on our results, NOM of BSI in geriatric patients is safe. LEVEL OF EVIDENCE: Therapeutic, level IV.